Small RNA Sequencing Identifies PIWI-Interacting RNAs Deregulated in Glioblastoma—piR-9491 and piR-12488 Reduce Tumor Cell Colonies In Vitro - Bartos, Michael; Siegl, Frantisek; Kopkova, Alena; Radova, Lenka; Oppelt, Jan; Vecera, Marek; Kazda, Tomas; Jancalek, Radim; Hendrych, Michal; Hermanova, Marketa; Kasparova, Petra; Pleskacova, Zuzana; et al. (Frontiers in Oncology, 2021)
Glioblastoma (GBM) is the most frequently occurring primary malignant brain tumor of astrocytic origin. To change poor prognosis, it is necessary to deeply understand the molecular mechanisms of gliomagenesis and identify new potential biomarkers and therapeutic targets. Piwi-interacting RNAs (piRNAs) help in genome stability maintaining and their deregulation has already been observed in many tumors. Recent studies suggest that these molecules could play also important role in the glioma biology. To determinate GBM associated piRNAs, we performed small RNA sequencing analysis in the discovery set of 19 GBM and 11 non-tumor brain samples followed by TaqMan qRT-PCR analyses in the independent set of 77 GBM and 23 non-tumor patients. Obtained data were subsequently bioinformatically analyzed. Small RNA sequencing revealed 58 significantly deregulated piRNA molecules in GBM samples in comparison with non-tumor brain tissues. Deregulation of piR-1849, piR-9491, piR-12487 and piR-12488 was successfully confirmed in the independent groups of patients and controls (all p < 0.0001); and piR-9491 and piR-12488 reduced GBM cells' ability to form colonies in vitro. In addition, piR-23231 was significantly associated with the overall survival of the GBM patients treated with Stupp regimen (p = 0.007). Our results suggest that piRNAs could be a novel promising diagnostic and prognostic biomarkers in GBM potentially playing the important roles in gliomagenesis.